The Impact of the Fuel Adjustment Mechanism on Economic Efficiency - Gollop, Frank M.; Karlson, Stephen H. (The Review of Economics and Statistics, 1978)
Automatic fuel adjustment mechanisms (FAM), which allow utilities to charge higher rates as fuel costs increase, are shown to disrupt the balance of economic efficiency provided for by regulatory lag. A model is developed to analyze efficiency changes caused by asymmetrical inputs and to examine the economic implications of broadening FAM to include the cost of labor, supplies, and purchased power. The conclusions are reached that efficiency is promoted by regulatory lag and formal hearings and that policies that circumvent these procedures reward inefficient behavior in terms of utility investment decisions. 13 references.